Pengaruh Penggunan Media Edpuzzle Terhadap Keterampilan Menulis Teks Negosiasi Kelas X SMK Marisi Medan - Gaol, Chyntia Renata Romauli Lumban; Panggabean, Sarma; Wulan, Eka Putri Saptari (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to analyze the influence of using Edpuzzle media on the negotiation text writing skills of grade X students at SMK Marisi Medan. The research method used was quasi-experimental with a pretest-posttest control group design. The research population consisted of 148 students, with a sample of 43 students divided into two groups: an experimental class (X OTKP, 21 students) that used Edpuzzle media and a control class (X AKL, 22 students) that used conventional learning. The research instrument was a negotiation text writing test assessed based on five aspects: text structure, type of negotiation, linguistic rules, purpose, and characteristics of negotiation texts. The results showed that there was no significant difference between the two groups at the pretest (p = 0.162), indicating initial ability equivalence. After the intervention, the average posttest score of the experimental group (60.19) was significantly higher than that of the control group (45.64) with p = 0.001. Gain score analysis showed an increase of 54.14% in the experimental group and 29.40% in the control group. The effect size (Cohen's d = 1.09) was in the large category, indicating that the use of Edpuzzle had a substantial impact. The conclusion of this research is that Edpuzzle media is effective in improving students' negotiation text writing skills. The implication is that this media can be integrated into Indonesian language learning to support more interactive and contextual learning, especially at the vocational high school (SMK) level.